2016
DOI: 10.31524/bkkmedj.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Job Stress among Ambulance Nurses in Bangkok, Thailand.

Abstract: R ecently, the socio-economic development, from an industrial perspective has transformed a lot. This rapid change affects the pattern of living of every occupation. The nursing professional, in particular, is one among healthcare professionals that tends to get occupational stress physically and emotionallyfacing with patient's suffering, pain, and even death. 1 Additionally, advances in medical technology apparently create more expectations and demand for nursing services. 2 The nurse is socially alerted not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…Adequate knowledge and experience are among the main requirements for sound decision making in emergency situations because EMS providers have not the permission to use the trial and error method during their missions [31]. In line with our findings, a former study showed that due to their limited decision making skills, EMS providers with limited professional experience undergo higher levels of stress [32]. Our participants also referred to any factor which delayed and interrupted their care provision as an occupational stressor.…”
Section: Critical Conditions Of Ems Provisionsupporting
confidence: 86%
“…Adequate knowledge and experience are among the main requirements for sound decision making in emergency situations because EMS providers have not the permission to use the trial and error method during their missions [31]. In line with our findings, a former study showed that due to their limited decision making skills, EMS providers with limited professional experience undergo higher levels of stress [32]. Our participants also referred to any factor which delayed and interrupted their care provision as an occupational stressor.…”
Section: Critical Conditions Of Ems Provisionsupporting
confidence: 86%
“…Our study found a significant relationship between work experience and stress, anxiety, and depression; the more experienced the PHEM personnel, the higher the levels of stress, anxiety, and depression. According to Sakko Onsri et al (2016), 33% of PHEM personnel with over 10 years of work experience had a high level of stress [ 36 ], which was consistent with our findings. One of the reasons for this finding is that people with more work experience are more likely to have underlying diseases and family issues, which are in turn associated with psychological problems [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, effective communication between both employer and employees help to ensure any clarification about the jobs assigned is clear. In fact, comprehensive clarification towards any issues can help to reduce stress in the workplace (Sakkomonsri & Kaewboonchoo, 2016). Furthermore, this research findings showed that most of the respondents have served MPOB for more than 10 years.…”
Section: Results Of Regression Analysismentioning
confidence: 65%
“…Based on Mabiza, Conduah & Mbohwa (2017) research findings, there was a tremendous change in a work environment today that was derived from the innovation of technology, customer's demand and valuable human capital. Consequently, all those changes actually influence the pattern of every occupation and living (Sakkomonsri & Kaewboonchoo, 2016). In addition, job stress does not influence individual's physical and mental health only, but also brings cost to the organization (Safaria, Othman & Wahab, 2010).…”
Section: Literature Review Job Stressmentioning
confidence: 99%
See 1 more Smart Citation